Penerapan Analisis SWOT Untuk Pengembangan Strategi Pemasaran UMKM Ayam Penyet Bang Iwan - Nanda Ismail Hasan; Barnard Defano Putra; Muhammad Zahran Sulthon; Muhammad Ridho; Rafil . (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study analyzes the internal and external conditions of the Ayam Penyet Bang Iwan MSME in Pekanbaru and formulates marketing strategies using SWOT analysis. The research employs a qualitative approach with a case study design; informants were selected purposively (the owner, employees, and customers). Data were collected through in-depth interviews, observation, and documentation, validated through source and method triangulation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The results indicate that the main strengths include raw material quality, lower prices, good relationships with suppliers, and an online application rating above 4.7/5; the weaknesses include a less strategic location, limited dining and parking space, and limited human resources. The greatest opportunities stem from leveraging food delivery platforms (Gojek/Grab/ShopeeFood), which contribute more than 80% of revenue, and an still-open market, while the main threats are competitors offering very low prices and fluctuations in raw material costs. The priority strategy lies in the S–T quadrant: maintaining product quality and taste consistency to sustain customer loyalty, strengthening supply efficiency through supplier negotiations, and improving service and parking management to enhance competitiveness.